The dead room - Kwok, Zong Han (Nanyang Technological University, 2023)
The Dead Room is an installation portraying humankind’s violation toward the natural environment around us. Living rooms are traditionally spaces where humans form social connections, seek comfort in the refuge of personal territories, and share common bond with one another. We tend to forget that the materials used to create such spaces are traditionally wood, which comes from trees that are also living beings. The Dead Room aims to portray humankind’s dominance over other living creatures through reimagining a living room space.